Environmental policy instruments for investments in backstop technologies under present bias - An application to the building sector - Fabian Arnold; Amir Ashour Novirdoust; Philipp Theile (Institute of Energy Economics at the University of Cologne (EWI), 2023)
Governments worldwide have set targets to reduce greenhouse gas emissions from the residential sector to zero. Policy instruments, such as carbon pricing or subsidies, are being discussed and implemented to achieve these targets. If individuals exhibit present bias, Heutel (2015) has shown that optimal policies targeting investments in the efficiency state of externality-producing durable goods and their usage consist of two components, one aimed at the externality and one aimed at the present bias. We generalize Heutel's theoretical model by defining a larger technology set. This allows us to represent the dependence of fuel prices and emission intensities on technologies used in the building sector and to include a zero emission backstop technology. We first examine the effect of this model generalization on Heutel's main propositions, assuming still that the backstop technology is not optimal. Second, we extend this examination to the case when the backstop technology is optimal. In a stylized case study for a representative building in Germany, we numerically estimate magnitudes of the present bias effect on investment and heating decisions, emissions, policies, and deadweight loss. We show that as long as social costs of carbon and the corresponding CO2 price are not high enough to make the backstop technology optimal, Heutel's proposition holds that optimal policies must consist of two components. Contrary to Heutel's proposition, if the social costs of carbon and the CO2 price are high enough, a single instrument can address present bias. While the level of this single instrument, i.e., a tax or subsidy, depends on the level of present bias, we find that there exists a tax-subsidy combination that is optimal regardless of the level of present bias.
Keywords: D15; D62; D91; H23; Q48; Q58; 330; Present bias; policy; heating investments; durable goods; climate neutrality